Chapter 4 Bob Dylan and the Invasion of Mexico - Rachwał, Tadeusz (Taylor & Francis, 2021)
All Along Bob Dylan: America and the World offers an important contribution to thinking about the artist and his work. Adding European and non-English speaking contexts to the vibrant field of Dylan studies, the volume covers a wide range of topics and methodologies while dealing with the inherently complex and varied material produced or associated with the iconic artist. The chapters, organized around three broad thematic sections Geographies, Receptions and Perspectives, address the notions of audience, performance and identity, allowing to map out the structure of feeling and authenticity, both, in the case of the artist and his audience. Taking its cue from the collapse of the so-called high-/ low culture split following from the Nobel Prize, the book explores the argument that Dylan (and all popular music) can be interpreted as literature and offers discussions in the context of literary traditions, or visual culture and music. This contributes to a nuanced and complex portrayal of the seminal cultural phenomenon called Bob Dylan.